Aberrant sialylation in ovarian cancers. Issue 4 (April 2020) - Lee, Wen-Ling; Wang, Peng-Hui
Abstract : Sialylation (the covalent addition of sialic acid to the terminal end of glycoproteins or glycans), tightly regulated cell- and microenvironment-specific process and orchestrated by sialyltransferases and sialidases (neuraminidases) family, is one of the posttranslational modifications, which plays an important biological role in the maintenance of normal physiology and involves many pathological dysfunctions. Glycans have roles in all the cancer hallmarks, referring to capabilities acquired during all steps of cancer development to initiate malignant transformation (a driver of a malignant genotype), enable cancer cells to survive, proliferate, and metastasize (a consequence of a malignant phenotype), which includes sustaining proliferative signaling, evading growth suppressor, resisting cell apoptosis, enabling replicative immortality, inducing angiogenesis, reprogramming of energy metabolism, evading tumor destruction, accumulating inflammatory microenvironment, and activating invasion and accelerating metastases. Regarding the important role of altered sialylation of cancers, further knowledge about the initiation and the consequences of altered sialylation pattern in tumor cells is needed, because all may offer a better chance for developing novel therapeutic strategy. In this review, we would like to update alteration of sialylation in ovarian cancers.